Implementación de un sistema de microgeneración hidráulica para garantizar la calidad de suministro electrico en voltaje y frecuencia - Areyuna Salazar, Francisco Xavier (2016)
Today has been an increase in microgeneration, especially in places that because of its geography makes it impossible the arrival of electric cables of conventional energy and in compliance with the change of the energy matrix, aiming to contribute to the use of sources alternatives. This project emphasizes the study of the hydro potential water potential of the “Hacienda San Nicolas” in the sector “Virgen de Guadalupe”, Saragosin neighborhood of Juan Montalvo Parish, city of Latacunga (Latitude: 0° 56’ 9.69’ S; Longitude: 78° 32’ 48.18 ‘ O), the study threw flow values of 5 lt/s at a height of approximately of 14 m which provides a pressure of 19.9 psi, and a depression angle of 28 degrees generating an average maximum electrical potential of 583 Watt according to losses enables effective generation of 400w which will provision of electricity to a network of luminaires.